2002
DOI: 10.1002/mus.10132
|View full text |Cite
|
Sign up to set email alerts
|

New evidence for a presynaptic action of prednisolone at neuromuscular junctions

Abstract: The action of prednisolone at the neuromuscular junction was studied in mouse isolated phrenic nerve-diaphragm and rat external popliteal/sciatic nerve-tibialis anterior muscle preparations. Prednisolone (0.03 mM and 0.3 mM) did not alter the twitch-tension in phrenic nerve-diaphragm preparations after 120 min, but increased the frequency (170 +/- 4%) and amplitude (200 +/- 13%) of miniature end-plate potentials. Quantal content was not influenced by the glucocorticoid treatment. Prednisolone (400 microg/kg) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…End-plate potentials were recorded in mouse ''glycerol-shocked'' diaphragms as described by Dal Belo et al (2002). End-plate potentials were corrected for non-linear summation of the quantal components (Martin 1955;Elmqvist & Quastel 1965) using the equation EPP c Ω[(EPP u (RPªRVP)]/RPªRVPªEPP u ), where EPP c is the corrected end-plate potential, EPP u is the uncorrected end-plate potential, RP is the resting potential and RVP is the reversal potential of the end-plate potential.…”
Section: Methodsmentioning
confidence: 99%
“…End-plate potentials were recorded in mouse ''glycerol-shocked'' diaphragms as described by Dal Belo et al (2002). End-plate potentials were corrected for non-linear summation of the quantal components (Martin 1955;Elmqvist & Quastel 1965) using the equation EPP c Ω[(EPP u (RPªRVP)]/RPªRVPªEPP u ), where EPP c is the corrected end-plate potential, EPP u is the uncorrected end-plate potential, RP is the resting potential and RVP is the reversal potential of the end-plate potential.…”
Section: Methodsmentioning
confidence: 99%
“…First, steroids have a direct facilitatory effect at the impulse-generating end of the motor nerve axon, and they act presynaptically to stimulate the synthesis and release of acetylcholine [19202122]. In addition, steroids amplify neuromuscular transmission by the predominant activation of presynaptic facilitatory adenosine A 2A receptors leading to synaptic vesicle redistribution [23].…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, the concentration of acetylcholine may be high enough at muscle-type nicotinic acetylcholine receptors, and non-depolarizing NMBs competitively inhibit the binding of acetylcholine to the receptors. In the animal study using mouse isolated phrenic nerve-diaphragm and rat external popliteal/sciatic nerve-tibialis anterior muscle preparations, it was observed that dexamethasone and prednisolone prevented neuromuscular block induced by d-tubocurarine via aforementioned mechanism [2122]. Therefore, an increased dose of d-tubocurarine is sufficient for neuromuscular block [22].…”
Section: Discussionmentioning
confidence: 99%
“…Tacrolimus has an action of increasing GR transactivity from cytoplasm to nucleus, promoted with loss of FKBP proteins and replacement with transported molecules such as PP5 26 . The facilitatory effect of tacrolimus on steroids pharmacology should also contribute to the steroid-induced increase of acetylcholine (ACh) release from the nerve terminal; the steroids interacts directly with the active transport of choline in the nerve terminal, resulting in an increased number of ACh molecules (increased ACh quantal size) 27 . These mechanisms of action of tacrolimus may account for the beneficial effect of this immunomodulating drug when given early after thymectomy in patients with MG to achieve remission and to reduce the post-thymectomy latency period until CSR is fully consolidated.…”
Section: Discussionmentioning
confidence: 99%